Incidence of nutritional support complications in patient hospitalized in wards. Multicentric study (2011)
ABSTRACT: Introduction: Nutritional support generates complications that must be detected and treated on time. Objective: To estimate the incidence of some complications of nutritional support in patients admitted to general hospital wards who received nutritional support in six high-complexity institutions. Methods: Prospective, descriptive and multicentric study in patients with nutritional support; the variables studied were medical diagnosis, nutritional condition, nutritional support duration, approach, kind of formula, and eight complications. Results: A total of 277 patients were evaluated; 83% received enteral nutrition and 17% received parenteral nutrition. Some 69.3% presented risk of malnourishment or severe malnourishment at admittance. About 35.4% of those receiving enteral nutrition and 39.6% of the ones who received parenteral nutrition had complications; no significant difference per support was found (p= 0.363). For the enteral nutrition, the most significant complication was the removal of the catheter (14%), followed by diarrhea (8.3%); an association between the duration of the enteral support with diarrhea, constipation and removal of the catheter was found (p < 0.05). For parenteral nutrition, hyperglycemia was the complication of highest incidence (22.9%), followed by hypophosphatemia (12.5%); all complications were associated with the duration of the support (p < 0.05). Nutritional support was suspended in 24.2% of the patients. Conclusions: Complications with nutritional support in hospital-ward patients were frequent, with the removal of the catheter and hyperglycemia showing the highest incidence. Duration of the support was the variable that revealed an association with complications. Strict application of protocols could decrease the risk for complications and boost nutritional support benefits.